The evolution of International business 1800-1945. Volume 8 : Foreign investment and economic development in China, 1840-1937 - Hou, Chi-ming. (London ; New York : Routledge, 2000)
A general picture of foreign investment in China. Foreign obligations of the Chinese government. Foreign direct investments in China. Framework of analysis of the effects of foreign investment. Determinants of foreign investment in China. Foreign investment and economic modernization. A dualistic economy. External aspects of foreign investment in China.
Keywords: Economics; Investments; Investments, Foreign -- China; China -- Economic conditions